A numerical and analytical investigation into non-Hermitian Hamiltonians - Wessels, Gert Jermia Cornelus (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MSc (Physical and Mathematical Analysis))--University of Stellenbosch, 2009.